Micro and macro analysis on household income, wealth and saving in the euro area - Juha Honkkila; Ilja Kristian Kavonius (European Central Bank (ECB), 2013)
The report on the Measurement of Economic Performance and Social Progress by Stiglitz, Sen and Fitoussi concludes that in the measurement of household welfare all material components should be covered, i.e. consumption, income and wealth, from both the micro as well as the macro perspective. Additionally, several other initiatives like the G20 finance ministers' and central bank governors' data gap initiative have emphasised to have an integrated micro-macro framework where consumption, income and wealth can be analysed. Current researches linking macro and micro information for the households have focused on income and consumption as these are the areas where most data sources are available. This paper extends the focus to household wealth using both survey data and financial accounts. It builds a link between wealth survey and national accounts' income concepts. This paper aims to create a first set of macroeconomic accounts that include wealth broken down by household groups.
Keywords: D30; D31; E01; E21; 330; balance sheets; financial accounts; households; wealth; wealth survey